2014
DOI: 10.1123/japa.2013-0015
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Individual, Social, and Physical Environmental Factors With Older Adults’ Television Viewing Time

Abstract: Sedentary behaviors (involving prolonged sitting) can be associated detrimentally with health outcomes. Older adults, the most sedentary age group, are especially at risk due to their high levels of television viewing time. This study examined individual, social, and physical environmental correlates of older adults' television viewing. Data on daily television viewing time, plus individual, social, and physical environmental factors were collected from 50,986 noninstitutionalized older adults (≥ 65 years) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
60
4
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 0 publications
12
60
4
5
Order By: Relevance
“…Finally, no socio-demographic correlates were related to any of the different contexts of sitting. The latter is in contrast with findings of previous studies [39, 14, 43, 44]. This may be because variables other than socio-demographics were included in the final step of the analyses.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Finally, no socio-demographic correlates were related to any of the different contexts of sitting. The latter is in contrast with findings of previous studies [39, 14, 43, 44]. This may be because variables other than socio-demographics were included in the final step of the analyses.…”
Section: Discussioncontrasting
confidence: 73%
“…Consequently, older adults may watch more TV if they have a partner who watches TV for many hours. On the other hand, previous research also showed that emotional loneliness was positively associated with TV viewing [39]. Among the participants who did sit during motorized transport, more active transport of the partner was associated with less sitting during motorized transport of the participant.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, logistic models were used and such association was observed in both models investigated (univariate and multiple). Other studies have also found an association between high leisure-time sedentary behavior and low functionality with the use of different tests and physical capacities 17,19,20,21 . One of the factors that may explain the fact of an individual to remain for long periods in sedentary behavior and affect functionality refers to the multifactorial origin of reduced musculoskeletal function and sedentary lifestyle can be considered an important factor for this problem 22 .…”
Section: Discussionmentioning
confidence: 94%
“…Van Cauwenberg et al (2014) found, for example, that access to facilities and safety from crime were both associated with older adults' television viewing time (indoor environmental factors were not considered). While the authors concluded that the observed effects of the physical environment were small and alterations in a single factor might not lead to clinically relevant changes, they suggested that the additive effect of several favourable factors might result in notable reductions in television viewing time (Van Cauwenberg et al, 2014, p. 514).…”
Section: The Environmental Correlates Of Pa and Sb In Older Adultsmentioning
confidence: 96%
“…Studies broaching these subjects have tended to concentrate on outdoor environments (e.g. Sugiyama & Ward Thompson, 2008;Van Cauwenberg et al, 2014) neglecting the home and other indoor spaces. For PA studies this is Brook¢eld et al 2 likely to be a function of the forms of PA investigated, e.g.…”
Section: The Environmental Correlates Of Pa and Sb In Older Adultsmentioning
confidence: 99%